2002
DOI: 10.1046/j.1365-2303.2002.00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid (partial) prescreening of cervical smears: the quality control method of choice?

Abstract: Rapid rescreening of all negative and inadequate smears is the quality control method of choice in the UK. The sensitivity of primary screening of laboratory and individual screeners are major indicators of screening quality and are dependent on the number of false negative smears found by rapid screening for their calculation. High sensitivity may indicate good quality primary screening or poor quality rapid review. Quantifiably high quality rapid rescreening is essential if these sensitivity figures are to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
47
0
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 10 publications
4
47
0
5
Order By: Relevance
“…As in previous studies in the literature, [22][23][24][25]29,31,32 our experience with RPS shows that it is an efficient and practical QC strategy in gynecologic cytology because it provides a measurable parameter with which to monitor the sensitivity of the Pap smears and allows for timely corrections before releasing the results to the clinicians.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…As in previous studies in the literature, [22][23][24][25]29,31,32 our experience with RPS shows that it is an efficient and practical QC strategy in gynecologic cytology because it provides a measurable parameter with which to monitor the sensitivity of the Pap smears and allows for timely corrections before releasing the results to the clinicians.…”
Section: Discussionsupporting
confidence: 61%
“…It has since been shown to be an efficient tool for QC in gynecologic cytology. [22][23][24][25][26] It is also reported to be as sensitive as RR in detecting abnormal smears. 33 Because all cases subsequently undergo routine full screening, it is possible to calculate the sensitivity of the prescreening procedure and, taking additional cases picked up on RPS into account, to better estimate the FNR for a laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,15,19 Nevertheless, one of the criticisms of the technique is that it permits only partial evaluation of the rapid reviewer's performance because only smears defined as negative in routine screening are revised; therefore, it is impossible for 100% rapid review to detect any abnormal cases that were not identified at routine screening. 20,21 Rapid prescreening permits the sensitivity not only of routine screening but also of rapid prescreening itself to be calculated. This is possible because all prescreened smears will be evaluated later at routine screening.…”
mentioning
confidence: 99%
“…As shown in various studies, it is possible to use abnormal cases identified both by rapid prescreening and by routine screening to monitor the performance of professionals in the daily routine of cytology laboratories. 6,9,20,[22][23][24][25] Nonetheless, it is only in Canada and the United Kingdom that this method is being routinely used. 4,25,26 Finally, the high rates of false-negatives constitute one of the principal problems faced by cytology laboratories.…”
mentioning
confidence: 99%